Telework and Work Intensity: Insights from an Exploratory Study in Portugal during the COVID-19 Pandemic - Glória Rebelo; Antonio Almeida; Joao Pedra (Administrative Sciences, 2024)
The expansion of teleworking and the digital transition movement have given companies and workers great flexibility, albeit with significant organisational consequences. The recent COVID-19 pandemic further reinforced the scale of this impact. Thus, the current research aims to understand whether the multiple dimensions of telework have impacted upon workers’ time management and work intensity through the unprecedented experiences during the pandemic and, in particular, to assess whether telework intensifies work, in what ways and the main reasons for this. The article analyses the literature on teleworking and work intensity and presents a documentary analysis on the subject, in addition to presenting the results of an exploratory study carried out in 2021 in Portugal which investigates the impact of teleworking on workers’ time management. The article underlines that although teleworking can increase a worker’s well-being by eliminating travel time, it presents several risks, namely it can intensify work through increased pressure to meet objectives and targets. Therefore, it is essential to develop research on the effects of telework, particularly assessing the relationship between telework and work intensification, as well as its effects on working conditions and workers’ well-being. This research will be an important resource for regulating labour laws and designing human resource management policies.